Museums of Łódź as an element of tourism space and the connection between museums and the city’s tourism image - Krakowiak, Beata (Turyzm/Tourism, 2015)
This article deals with the museum potential of Łódź. The first sections describe the kinds and significance of museums, their location in the city and the attractiveness of their collections, premises and organized events. The following sections describe the significance of museums in regard to attendance and the city’s tourism image.